Career sacrifice unpacked: From prosocial motivation to regret - Zikic, Jelena (Frontiers in Psychology, 2022)
In the ever more uncertain career context, many individuals engage in a form of career sacrifice at some point in their career journey; that is, giving up of certain career goals/actions or reshaping career decisions to accommodate specific work or life demands. This conceptual paper unpacks career sacrifice as an important yet little explored dimension of career decision making. Specifically, the paper examines possible triggers of career sacrifice as well as the diverse nature of career sacrifice, ranging from short-term (usually minor) type of sacrifice to more significant and long-term sacrifice. We explore the context of this type of career decision making, specifically the intersection of work and non-work-related triggers and conclude by discussing possible work and non-work outcomes both at the individual as well as organizational level. Career sacrifice outcomes range from enhanced career self-management and relational benefits to positive organizational contributions, but at times can also lead to regret. Areas for future research are identified, especially exploration of demographic and more macro level variables as possible moderators in career sacrifice decisions. Future theoretical development of career sacrifice is discussed too.